AMPK activation protects against diet induced obesity through Ucp1-independent thermogenesis in subcutaneous white adipose tissue - Pollard,AE; Martins,L; Muckett,PJ; Khadayate,S; Bornot,A; Clausen,M; Admyre,T; Bjursell,M; Fiadeiro,R; Wilson,L; Whilding,C; Kotiadis,VN; et al. (Nature Metabolism, 2019)
Obesity results from a chronic imbalance between energy intake and energy output but remains difficult to prevent or treat in humans. Adenosine monophosphate (AMP)-activated protein kinase (AMPK) is an important regulator of energy homeostasis1,2,3 and is a molecular target of drugs used for the treatment of metabolic diseases, including obesity4,5. Here we show that mice expressing a gain-of-function AMPK mutant6 display a change in morphology of subcutaneous white adipocytes that is reminiscent of browning. However, despite a dramatic increase in mitochondrial content, Ucp1 expression is undetectable in these adipocytes. In response to a high-fat diet (HFD), expression of skeletal muscle–associated genes is induced in subcutaneous white adipocytes from the gain-of-function AMPK mutant mice. Chronic genetic AMPK activation results in protection against diet-induced obesity due to an increase in whole-body energy expenditure, most probably because of a substantial increase in the oxygen consumption rate of white adipose tissue. These results suggest that AMPK activation enriches, or leads to the emergence of, a population of subcutaneous white adipocytes that produce heat via Ucp1-independent uncoupling of adenosine triphosphate (ATP) production on a HFD. Our findings indicate that AMPK activation specifically in adipose tissue may have therapeutic potential for the treatment of obesity.